2021
DOI: 10.1002/1878-0261.12929
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MRE11A by UBQLN4 leads to cisplatin resistance in patients with esophageal squamous cell carcinoma

Abstract: Resistance to standard cisplatin‐based chemotherapies leads to worse survival outcomes for patients with esophageal squamous cell carcinoma (ESCC). Therefore, there is an urgent need to understand the aberrant mechanisms driving resistance in ESCC tumors. We hypothesized that ubiquilin‐4 (UBQLN4), a protein that targets ubiquitinated proteins to the proteasome, regulates the expression of Meiotic Recombination 11 Homolog A (MRE11A), a critical component of the MRN complex and DNA damage repair pathways. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 47 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…It was reported that overexpression of UBQLN4 in neuroblastoma cells increased the sensitivity of PARP inhibitors [ 4 ]. However, Murakami et al found that knocking down UBQLN4 in esophageal squamous cell carcinoma increased cisplatin sensitivity [ 7 ], suggesting different roles of UBQLN4 played in various drugs. In line with previous studies, our results showed that there was a positive correlation between UBQLN4 CNV and olaparib sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that overexpression of UBQLN4 in neuroblastoma cells increased the sensitivity of PARP inhibitors [ 4 ]. However, Murakami et al found that knocking down UBQLN4 in esophageal squamous cell carcinoma increased cisplatin sensitivity [ 7 ], suggesting different roles of UBQLN4 played in various drugs. In line with previous studies, our results showed that there was a positive correlation between UBQLN4 CNV and olaparib sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, the role of UBQLN4 in cancers attracted increasing attention [ 6 , 7 ], although theories behind are premature. It was reported that the increase of UBQLN4 in neuroblastoma and melanoma decreased survival [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that UBQLN4 levels affect cisplatin sensitivity. 5,6 UBQLN4 levels were associated with increased cisplatin resistance in TNBC cell lines (Figure 1H). UBQLN4 depletion did not induce significant transcriptional changes in TNBC cell lines (Figure S1B-F) or reduce cellular proliferation (Figure S1G-J); however, it increased the sensitivity to cisplatin, whereas UBQLN4-OV led to cisplatin resistance (Figure 1I-K).…”
Section: E T T E R T O T H E E D I T O R Ubqln4 Promotes Sting Protea...mentioning
confidence: 95%
“…Further analysis provides a rationale for this finding by showing that UBQLN4 overexpression protects cells from acute genotoxic stress through enhancing the NHEJ-mediated sealing of DSBs, as NHEJ-driven mutagenesis is likely to be selected in cancer cells due to its error-prone mechanism [85]. Moreover, UBQLN4 binds to MRE11 and promotes MRE11 degradation, leading to cisplatin-resistance in cancer cells, i.e., esophageal squamous cell carcinoma (ESCC) [93]. Similarly, MRE11 ubiquitination is also involved in bladder cancer.…”
Section: Ubiquitination and Ubiquitin-like Modification Of Mre11mentioning
confidence: 99%